Decolonising the Reading of Psalm 8 in an African (Yoruba) Context - Adamo, David Tuesday (Journal for Semitics, 2020)
Psalm 8 is one of the most important psalms of praise to YHWH. Unlike other psalms of praise, this psalm begins with the name of God, Yahweh, which clearly and unmistakeably expresses that he is glorious throughout his creation. Psalm 8 not only expresses the glory of Yahweh, but also the value and responsibility of humanity. This article examines how Psalm 8 is read and interpreted in an African/Yoruba religious and cultural tradition as a psalm of protection, healing, and success. Some archaeological evidence seems to support the use of the Bible that way. The effectiveness of such use in the African/Yoruba Christian tradition is not doubted because a strong faith is behind it. Such use represents an African/Yoruba affirmation of faith in Yahweh who will repeat the miracles of healing, protection, and success that he had performed in ancient Israel in their present lives.
paid
Keywords: Africa; Old Testament; Yoruba; creation; praise psalm